Solving of fuzzy Multiobjective Optimization Problem Using The WeightingMethodflow in a channel filled with porous medium - Mohammed, Osama; Fadel, Fadhel; Abbas, Iraq (Iraqi Journal of Science, 2024)
In this paper fuzzy multiobjective optimization problem with or withoutconstraints is presented. The weighted method is considered to formulate the fuzzymultiobjective problem as a fuzzy singleobjective function and then Iskandars’approach is used to solve the resulting fuzzy optimization problem.